Sapar Alliance Movement (Syarekat Perjuangan Rakyat) Against Geothermal Project In Padarincang Prakasak Mountain - Sulistyaningrum, Dyah; Ramadhan, Gilang (Journal of Social Politics and Governance (JSPG), 2023)
Mount Prakasak is a protected forest located in Batukuwung village, Padarincang district, Serang Regency, Banten Province which has the potential for geothermal energy to be used as electricity. This study aims to describe the rejection of the Padarincang community who are members of the SAPAR (Syarekat Perjuangan rakyat) alliance movement against the development of geothermal projects. The research method used is descriptive qualitative, with data collection through interviews, observation, and documentation. This research shows that the Padarincang community who are members of the SAPAR alliance reject the construction of geothermal projects because they can damage the preservation of nature. Ecological damage due to geothermal exploration and exploitation activities that damage forests and is feared to cause significant natural damage that affects people's economic activities from the agricultural sector.